Tailoring IPM plans to fight a cloaked pest: helping smallholder farmers combat the sweetpotato weevil in sub-Saharan Africa - Chad A. Keyser; Frederick S. Walters; Haley Turner; Elka Armstrong; Jeff Davis; Brooke Bissinger; Brant Johnson; Agnes Alajo; Paul Musana; Joseph Odongo; Benard Yada; Milton A. Otema (CABI Agriculture and Bioscience)
Abstract Africa accounts for a significant portion of the world’s sweetpotato production where it is widely grown as a staple crop. In sub-Saharan Africa (SSA), sweetpotato serves as an important year-round source of calories and nutrition, a form of income for smallholder and pre-commercial farmers, and is increasingly used as silage for animal feed. However, yield per hectare is considerably lower in SSA than from other regions primarily due to sweetpotato weevils (SPW, Cylas spp., Coleoptera: Brentidae). Weevil feeding causes physical damage to the root and can induce chemical responses that give the storage root a bitter taste, both of which make them unmarketable. Commercial growers in many developed countries rely on frequent chemical treatments and strict quarantine regulations to control SPW, however, this approach is currently not practical for many areas of SSA. In this paper we, (1) outline factors that contribute to SPW infestation; (2) review available strategies and ongoing research for control of SPW, including chemical pesticides, biological control (macro-organismal as well as microbial control), cultural practices, selective breeding, and biotechnology; and (3) discuss the potential for implementing an integrated pest management (IPM) approach that leverages a combination of techniques. We rationalize that a multifaceted strategy for SPW control will improve both the quantity and quality of sweetpotato production in Africa.